2014
DOI: 10.1002/etc.2564
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of organochlorine contaminants and ethoxyresorufin‐o‐deethylase activity in southern California round stingrays (Urobatis halleri) exposed to planar aromatic compounds

Abstract: While contaminant concentrations have been reported for elasmobranchs around the world, no studies have examined bioaccumulation patterns across male and female age classes. The round stingray (Urobatis halleri) is a local benthic species that forages near areas of high organochlorine contamination and represents a good elasmobranch model. Polychlorinated biphenyls (PCBs), DDT, and chlordanes were measured in juvenile and adult male and female stingrays from areas in southern California, USA (n = 208), and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Rather than representing an accessible energy reserve for growth, the larger embryos with smaller liver weight at the reference site could indicate that reference male embryos are more efficient at converting maternal resources (i.e., histotroph) into extrahepatic somatic growth because they had a relatively heavier total body mass. These findings support earlier evidence of adult male vulnerability to contaminants at the same sites (Lyons et al ), where males from the contaminated site exhibited biochemical responses to exposure but females did not. The liver has a propensity to accumulate organochlorine contaminants, making it particularly susceptible to contaminant effects.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Rather than representing an accessible energy reserve for growth, the larger embryos with smaller liver weight at the reference site could indicate that reference male embryos are more efficient at converting maternal resources (i.e., histotroph) into extrahepatic somatic growth because they had a relatively heavier total body mass. These findings support earlier evidence of adult male vulnerability to contaminants at the same sites (Lyons et al ), where males from the contaminated site exhibited biochemical responses to exposure but females did not. The liver has a propensity to accumulate organochlorine contaminants, making it particularly susceptible to contaminant effects.…”
Section: Discussionsupporting
confidence: 90%
“…Although previous studies documented significant differences in PCB concentrations in the livers of reference and contaminant‐exposed stingrays (Lyons et al ; Sawyna et al ), this observation was confirmed by measuring PCB contaminants in a subset of female liver samples ( n = 16, 8 from each location). Fifty‐three PCB congeners (Supplemental Data, Table S1) were analyzed following the methods of Lyons et al (). As expected, hepatic PCB concentrations averaged significantly (4‐fold) higher in contaminant‐exposed females than reference females (Welch's t test, t 8 = 3.09, p < 0.02; Supplemental Data, Table S2).…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…Compared to other benthic elasmobranchs in this region, the angel sharks sampled from this study had much greater hepatic concentrations of total organochlorines (10.1 ± 7.7 lg/g ww) than that measured from other local benthic elasmobranchs such as male round stingrays Urobatis halleri (2.1 ± 1.7 lg/g ww; Lyons et al, 2014) and bat rays Myliobatis californica (5.0 ± 3.5 lg/g ww, n = 4; unpublished data). In addition, the average DDT:PCB ratio was much greater in the female angel sharks (4.1 ± 0.7) than these two other elasmobranch species (0.09 ± 0.06 and 0.9 ± 0.8, respectively).…”
mentioning
confidence: 94%